Osborn's brain : imaging, pathology, and anatomy - Osborn, Anne G., 1943-; Salzman, Karen L.; Linscott, Luke L. (Philadelphia, PA : Elsevier, 2024)
"Combining informative, meticulously crafted prose with more than 4,000 high-quality images, Osborn's Brain, third edition, is a comprehensive, easy to understand, and visually stunning learning curriculum from highly esteemed author Dr. Anne G. Osborn. This fully revised edition provides a solid framework for understanding the complex subject of brain imaging, integrating relevant information from Dr. Osborn's entire career of accumulated knowledge, experience, and interest in neuropathology, neurosurgery, and clinical neurosciences. While neuroradiologists will find intriguing, thought-provoking insights included especially for them in every chapter, Osborn's Brain is an excellent review resource for physicians at all levels of expertise--from seasoned radiologists and neurosurgeons to new and senior residents or fellows." --
Section 1. Trauma -- Trauma Overview -- Primary Effects of CNS Trauma -- Secondary Effects amd Sequelae of CNS Trauma -- Section 2. Nontraumatic Hemorrhage and Vascular Lesions -- Approach to Nontraumatic Hemorrhage and Vascular Lesions -- Spontaneous Parenchymal Hemorrhage -- Subarachnoid Hemorrhage and Aneurysms -- Vascular Malformations -- t Arterial Anatomy and Strokes -- Venous Anatomy and Occlusions -- t Vasculopathy -- Section 3. Infection, Inflammation, and Demyelinating Diseases -- t Approach to Infection, Inflammation, and Demyelination -- Congenital, Acquired Pyogenic, and Acquired Viral Infections -- Tuberculosis and Fungal, Parasitic, and Other Infections -- HIV/AIDS -- Demyelinating and Inflammatory Diseases -- Section 4. Neoplasms, Cysts, and Tumor-Like Lesions -- Introduction to CNS Neoplasms and Nonneoplasms Cysts -- Adult-Type Diffuse Gliomas -- Pedriatric-Type Diffuse Low-Grade Gliomas -- Circumscribed Astrocytic Gliomas -- Glioneuronal and Neuronal Tumors -- Ependymal Tumors -- Choroid Plexus Tumors -- Embryonal Tumors -- Pineal and Germ Cell Tumors -- Cranial Nerve Tumors -- Meningiomas and Melanocytic Lesions -- Mesenchymal, Nonmeningothelial Tumors -- Hematolymphoid and Hematopoietic Tumors -- Sellar Region Tumors and Tumor-Like Conditions -- Metastases and Paraneoplastic Syndromes -- Nonneoplastic Cysts -- Miscellaneous Tumors and Tumor-Like Conditions -- Section 5. t Toxic, Metabolic, Degenerative, and CSF Disorders -- Approach to Toxic, Metabolic, Degenerative, and CSF Disorders -- Toxic Encephalopathy -- t Inherited Metabolic Disorders -- Acquired Metabolic and Systemic Disorders -- Dementias and Brain Degenerations -- Hydrocephalus and CSF Disorders -- Section 6. Congenital Malformations and Genetic Tumor Syndromes -- Approach to Congenital Malformations -- Posterior Fossa Malformations -- Commissural and Cortical Maldevelopment -- Holoprosencephalies, Related Disorders, and Mimics -- Genetic Tumor Syndromes Involving the CNS -- Vascular Neurocutaneous Syndromes -- Anomalies of the Skull and Meninges
Osborn's brain : imaging, pathology, and anatomy / Anne G. Osborn. Second edition. ©2018
Includes bibliograpical references and index
Keywords: Brain -- Pathophysiology; Central nervous system -- Diseases; Brain -- Imaging; Central Nervous System Diseases